Analysis of exciton reflection spectrum of 2H-PbI₂ layered single crystals with atomically clean surface - Dorogan, V.G.; Zhydkov, V.O.; Motsnyi, F.V.; Smolanka, O.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
We performed the computer modelling of the dispersion dependences of real ε₁(E) and imaginary ε₂(E) parts of complex dielectric function ε(E) for 2H-PbI₂ crystals with atomically clean surface at the temperature 5 K and the light polarization E⊥C and determined the energy position of the exciton bands and the parameters of the critical points. The obtained data allowed us to conclude the exciton spectra of this semiconductor can be described in terms of a single Wannier series with a large ground-state anomaly caused by a repulsive central-cell correction due to the cationic character of the exciton.